Indications of a positive feedback between coastal development and beach nourishment. Issue 12 (21st December 2016) - Armstrong, Scott B.; Lazarus, Eli D.; Limber, Patrick W.; Goldstein, Evan B.; Thorpe, Curtis; Ballinger, Rhoda C.
Abstract: Beach nourishment, a method for mitigating coastal storm damage or chronic erosion by deliberately replacing sand on an eroded beach, has been the leading form of coastal protection in the United States for four decades. However, investment in hazard protection can have the unintended consequence of encouraging development in places especially vulnerable to damage. In a comprehensive, parcel‐scale analysis of all shorefront single‐family homes in the state of Florida, we find that houses in nourishing zones are significantly larger and more numerous than in non‐nourishing zones. The predominance of larger homes in nourishing zones suggests a positive feedback between nourishment and development that is compounding coastal risk in zones already characterized by high vulnerability. Key Points: We examine property‐scale data from over 12, 000 single‐family shorefront homes along more than 1400 km of coastline in Florida, USA Houses are significantly larger and more numerous in beach‐nourishment zones This spatial correlation suggests the emergence of a positive feedback between coastal development and beach nourishment